Lessons learned from testing cardiac channelopathy and cardiomyopathy genes in individuals who died suddenly: A two‐year prospective study in a large medical examiner's office with an in‐house molecular genetics laboratory and genetic counseling services. Issue 2 (22nd August 2019) - Williams, Nori; Manderski, Elizabeth; Stewart, Sarah; Bao, Ruijun; Tang, Yingying
Abstract: This is a comprehensive review and analysis of 254 cases tested consecutively in the in‐house College of American Pathologist‐accredited molecular genetics laboratory within the New York City Office of Chief Medical Examiner between October 2015 and February 2018, using a multigene cardiac panel composed of 95 genes associated with cardiac channelopathy and cardiomyopathy. Demographics, autopsy findings, medical history, and postmortem genetic testing results were collected for each case. The majority of decedents were adults (>25 years old, 52.7%), followed by infants (<12 months, 25.6%), young adults (19–25 years old, 11.4%), and children (1–18 years old, 10.2%). There were more males (64.2%) than females (35.8%). The racial/ethnic composition of decedents was 40.2% Black, 29.9% Hispanic, 22.4% White, 5.1% Asian/Pacific Islander, and 2.8% mixed/unspecified. Overall, 45.7% of decedents had a negative autopsy, and the remaining had one to four cardiac findings (cardiac hypertrophy, dilation, atherosclerosis, and fatty change). Twenty‐seven pathogenic/likely pathogenic variants (P/LP) and 99 variants of uncertain significance (VUS) were identified in 10.6% and 39% of decedents respectively. P/LP and VUS were found in 51 cardiac genes of the total 95 genes, where MYBPC3, TTN (predicted truncating variants), KCNH2, RYR2 and DSP genes had more than two P/LP variants identified. Among the 73 decedents who were suspected of having cardiac arrhythmia or cardiomyopathy, 20.3% had P/LP variants and 47.9% had VUS; among 23 decedents who had hypertensive cardiovascular diseases and 20 decedents with a history of substance use, 13% and 30% had P/LP variants, respectively. There were 26 referrals from medical examiners for genetic counseling and the outcomes are discussed. The study demonstrates characteristics of the diverse population typically seen by medical examiners in an urban center and our results support a broader implementation of molecular testing in sudden death. Abstract :